Clusterin facilitates metastasis by EIF3I/Akt/MMP13 signaling in hepatocellular carcinoma - Wang, Cun (Oncotarget, 2014)
Clusterin (CLU) is a stress-induced chaperone that confers proliferative and survival advantages to cancer cells. However, effects and molecular mechanisms of CLU in hepatocellular carcinoma (HCC) metastasis are still unknown. In this study, HCC tissue array (n = 198) was utilized to investigate correlation between CLU expression and clinicopathological features. Overexpression of CLU in HCC tissues was correlated with shorter overall survival and higher tumor recurrence. In vitro and in vivo assays demonstrated that silencing CLU attenuated the invasion and metastasis of HCC cells, whereas ectopic overexpression of CLU resulted in the forced metastasis of HCC cells. We also revealed that CLU activated Akt signaling through complexing with eukaryotic translation initiation factor 3 subunit I (EIF3I), which in turn promoted matrix metalloproteinase 13 (MMP13) expression and HCC metastasis. Positive correlations between CLU and MMP13, p-Akt, or EIF3I were found in HCC tissues. We further observed that CLU knockdown using the CLU inhibitor OGX-011 significantly suppressed HCC metastasis in two metastatic models through inhibiting EIF3I/Akt/MMP13 signaling. These findings indicate that CLU is an independent predictive factor for prognosis of HCC and it facilitates metastasis through EIF3I/Akt/MMP13 signaling. CLU suppression using OGX-011 may represent a promising therapeutic option for suppressing HCC metastasis.